Advances in Triboelectric Nanogenerators for Microbial Disinfection - Jinyoung Jeon; Donghyeon Kang; Sang-Woo Kim (Micromachines)
The global COVID-19 pandemic has highlighted the pivotal role of microbial disinfection technologies, driving the demand for innovative, efficient, and sustainable solutions. Triboelectric technology, known for efficiently converting ambient mechanical energy into electrical energy, has emerged as a promising candidate to address these needs. Self-powered electro-based microbial disinfection using triboelectric nanogenerators (TENGs) has emerged as a promising solution. TENGs have demonstrated effective disinfection capabilities in various settings, including water, air, surfaces, and wounds. This review explores the advancements in TENG-based microbial disinfection, highlighting its mechanisms and applications. By utilizing triboelectric technology, it provides comprehensive insights into the development of sustainable and efficient solutions for microbial control across diverse environments.